Reimagining Matthean economic ethics in postcolonial South Africa - Hombana, Mphumezi (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2024)
This article investigates the intersection of economic justice and postcolonialism within post-1994 South Africa. Amid growing discourse on economic freedom and justice in both political and religious spheres, this article aims to elucidate the Matthean economic ethical principles and values – for both marginalised and affluent communities in postcolonial South Africa. By adopting a postcolonial framework, the study aims to uncover the underlying power dynamics, socio-economic inequalities, and historical legacies shaping the nation’s contemporary economic imbalances. Furthermore, the article explores the role of churches and religious leaders in addressing economic justice issues.Contribution: This article offers insights into how Matthean economic ethics can be adopted to confront systemic injustices and advocate for the economic empowerment and liberation of marginalised communities in post-1994 South Africa, emphasising the relevance of Matthean economic ethics.